AI in Companies' Production Processes: What Do Their CEOs Think? - Maldonado-Canca, Luis; Cabrera-Sánchez, Juan Pedro; Casado-Molina, Ana María; Bermúdez-González, Guillermo José (IGI Global, 2024)
The accelerated integration of Artificial Intelligence (AI) in comprehensive organizational management has marked a significant milestone in enhancing efficiency and productivity across all sectors. However, the effective adoption of this emerging technology faces significant challenges, such as ethical dilemmas, organizational barriers, and a notable deficit in relevant technological skills. This study embarks on a detailed analysis of the crucial determinants influencing the adoption of AI by companies, enhancing the UTAUT model with four new variables: Response Costs, Trust in AI, AI Anxiety, and Environmental Sustainability. Through surveys directed at over 400 CEOs of companies, this work reveals that facilitating conditions, performance expectancy, response costs, trust in AI, and AI anxiety determine the adoption of this new technology in their companies. These findings contribute to identifying which factors, from a managerial perspective, should be considered as more than sufficient reasons for AI to be implemented in their production processes.
Keywords: Empresas - Gestión - Innovaciones tecnológicas; Artificial Intelligence (AI); Internal Processes; Production Processes; AI Implementation; Response Costs; AI Anxiety; Trust in AI; Environmental Sustainability